COVD-02. ADAPTING RNA-NANOPARTICLE VACCINES FROM GLIOBLASTOMA TO SARS-COV-2. (9th November 2020) - Mendez-Gomez, Hector; Castillo, Paul; Jones, Noah; Qdaisat, Sadeem; Weidert, Frances; Mitchell, Duane; Sayour, Elias
Abstract: BACKGROUND: Glioblastoma (GBM) can be an effective teacher in the war on COVID-19, as an operative vaccine for either must elicit near-immediate protective responses that overcomes disease heterogeneity and immune suppression. Current prophylactic strategies against COVID-19 utilize mRNA vaccines targeting small fragments of the SARS-CoV-2 genome, but these may not induce robust T cell responses or elicit immunity quickly enough. OBJECTIVE: We sought to adapt an FDA-IND approved mRNA vaccine in GBM against COVID-19 for: 1) activation of near immediate immune responses, 2) targeting of full-length SARS-CoV-2 structural proteins, and 3) induction of bidirectional (B and T cell) adaptive immunity. METHODS: We utilized a novel engineering design that layers mRNA into a lipid-nanoparticle (NP) shell (much like an onion); this allows greater packaging of mRNA per particle to quickly boost innate/adaptive immune responses against full-length glioblastoma antigens or SARS-CoV-2 structural proteins. RESULTS: In small and large animal models, RNA-NPs safely mimic viremia activating the quiescent immune system in only a few hours for induction of protective immunity against its mRNA payload. RNA-NPs activate dendritic cells (DCs), upregulate critical innate gene signatures, and induce antigen-specific cellular and humoral immunity. We found that mice receiving SARS-CoV-2 spike RNA-NPs had more effector T cells after vaccination with significant memory recall expansion after in vitro re-stimulation with overlapping SARS-CoV-2 spike peptide mix. We also found increased release of MIP-1-alpha (i.e. CCL3) previously shown by our group (Mitchell et al. Nature 2015) to be responsible for Th1 mediated memory recall to infectious vaccine antigens in GBM patients. CONCLUSION: SARS-CoV-2 RNA-NPs elicit memory recall response after vaccination. We have obtained FDA-IND approval (BB-19304, Sayour) in GBM with SARS-CoV-2 specific amendment (BB-20871) underway to support first-in-human trials of RNA-NPs targeting both GBM and COVID-19.